Cold War literature : writing the global conflict - Hammond, Andrew, 1967- (Routledge studies in twentieth-century literature, 2006)
The Cold War was the longest conflict in a century defined by the scale and brutality of its conflicts. In the battle between the democratic West and the communist East there was barely a year in which the West was not organising, fighting or financing some foreign war. It was an engagement that resulted - in Korea, Guatemala, Nicaragua and elsewhere - in some twenty million dead. This collection of essays analyses the literary response to the coups, insurgencies and invasions that took place around the globe, and explores the various thematic and stylistic trends that Cold War hostilities.